ENGARUH KEGIATAN SEKTOR INDUSTRI,PERTAMBANGAN DAN TRANSPORTASI TERHADAP KUALITAS LINGKUNGAN DITINJAU DARI EMISI CO2 DI INDONESIA - Ayudhia Andarini; Idris Idris; Ariusni Ariusni (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2017)
Carbondioxyde emission is kind of green house gases that has highest concentration in he atmosphere than the ohers green house gases. The aim of this research is that analyzing influence of industry sector, mining sector, and transportation sector avtivities to the environment quality base on the carbondioxyde emission in Indonesia. This analysis used regression model with Ordinary Least Square method (OLS). Result of analysis indicate that Gross Domestic Product  (GDP) of industry sector has negative and significant  influence to carbondioxyde emission in Indonesia, with  significant value at 0.00,  Gross Domestic Product (GDP) of mining sector has positive and significant influence to carbondioxyde emission in Indonesia with significant value at 0.00 and Gross Domestic Product  (GDP) of transportation sector has positive and significant influence to Economic Growth in Indonesia, with significant value at 0.00. Then, Gross Domestic Product  (GDP) of industry sector, mining sector and transportation sector have significantly influence to Economic growth in Indonesia with significant value at 0.00 based on with the theory Environmental Kuznet Curve (EKC).